The resilience of food and beverage companies during the Covid-19 pandemic - Nathali, Dhea Khanti; Meliana, Meysih; Suwal, Palpasha (IAS Journal of Localities, 2023)
In the context of Covid-19 pandemic crisis, looking at companies survival has become a very important aspect. A crisis period becomes a test for a company’s resilience in facing external uncertainty that involving various aspects such as economic, social, and health. The aim of this research is to investigate to what extent of the companies in this sector are able to maintain stability, which is reflected in abnormal returns. This research applies quantitative method, and uses the normality test and the one sample test on capital market statistical data that reflects the company’s financial performance. The research questions involve what factors influence abnormal returns, how food and beverage companies adapt strategies during the pandemic, and the impact on operational and financial stability. The study results show that companies in this sector are succeeded in maintaining stability during the pandemic crisis. Recommendations for future studies include further exploration of factors that strengthen resilience that food and beverage companies are able to increase their survival in the future.